Critical sustainability insights in Indonesian village-owned enterprises / Satria Tri Nanda, Razana Juhaida Johari and Zuraidah Mohd Sanusi - Tri Nanda, Satria; Johari, Razana Juhaida; Mohd Sanusi, Zuraidah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
The unsustainable performance of Village-Owned Enterprises (VOEs) in Indonesia has emerged as a critical issue requiring immediate resolution. Many VOEs in Indonesia struggle to sustain their performance, necessitating an understanding of the underlying causes. This qualitative study utilized interviews with government officials at both ministry and village levels to identify root problems, along with a literature review to support deeper analysis. Based on these interviews and literature review, three main causes of unsustainable performance of VOE in Indonesia were identified: lack of leadership, lack of innovation, and lack of governance. This article addressed gaps in the sustainability literature for social organizations by adopting a comprehensive approach involving government, practitioners, and academics to examine barriers to the sustainability of VOEs in Indonesia.